Biochemically Investigation of the Effects of Nettle Seed Herbal Mixture on Alcohol Damaged Liver - A. ÇELİK; A. ERMIŞ; O. KAYGUSUZ; G. GÖRK (International Journal of Secondary Metabolite)
It was experimentally investigated in this research how protective Nettle Seed Herbal Mixture is against ethanol which causes oxidative stress in rats and causes toxic effects in the liver with chronic use. 20 4-month-old female Wistar male rats were used in the study. All rats in the study were fed with normal pellet Mouse food during the experiment. 10 week application was done by dividing the rats into four equal groups. Application method is orally drinking method. First group is the control group. The second group is the alcohol group. This group was given 30% ethanol in order to cause chronic alcoholisms. The third group was the alcohol+ Nettle Seed Herbal Mixture group and the rats in this group were given liquid, which was 30% ethanol,+ Nettle Seed Herbal Mixture extract. Fourth group was Nettle Seed Herbal Mixture extract group and the rats in this group were given liquid, which was Nettle Seed Herbal Mixture extract. At the end of ten weeks, within the first 24 hours, blood species were obtained from the animals under anesthesia using appropriate techniques. Serum ALT and AST values of the obtained blood samples were studied by enzymatic methods in "Roche Cobas 6000" device.. Biochemically ALT and AST enzyme values and statistical analysis with SPSS programe were done. No significant difference was found between these four groups at the end of the analysis because p value was bigger than 0,005.